How to Integrate ESD (Education for Sustainable Development) into STEM Education?: A Systematic Literature Review - Habibaturrohmah, Zuana; Kaniawati, Ida; Solihat, Rini; Nirbayati, Wahyu Fadzilla (Journal of Natural Science and Integration, 2023)
education to equip individuals with the knowledge, skills, abilities, and values necessary for personal development and societal contribution. This gave rise to the concept of education for sustainable development (ESD). Within this framework, STEM (science, technology, engineering, and mathematics) education is vital for preparing the younger generation to tackle societal challenges. Integrating ESD principles into STEM education is thus an effective approach to promote a sustainable future. This study aims to review existing empirical research on the implementation of STEM-ESD to explore various strategies for STEM-ESD learning. The PRISMA 2020 systematic literature review method was used, with Scopus as the primary database. Out of 160 collected articles, 20 met the criteria for thematic-qualitative analysis. This study finds that the strategies to integrate ESD into STEM education are: 1) Incorporating concepts of SDGs into STEM lessons, 2) Promoting hands-on activities and projects, 3) Designing real-world problems to apply STEM in addressing sustainability challenges, 4) Fostering partnerships with local communities, organizations, and industry stakeholders, and 5) Providing training and resources for educators to enhance their understanding of STEM-ESD teaching.Keywords: STEM education, Education for Sustainable Development, STEM-ESD, systematic literature review